Development of educational kit for IoT online learning - Nurulhuda Abdul Rahman; Muhammad Ridzuan Idris; Khairul Salleh Baharudin (Indonesian Institute For Counseling, Education and Therapy, 2020)
Internet of Thing (IoT) is one of the elements that drive the development of the Industrial Revolution (IR 4.0). Therefore, IoT has become the most important agenda in the globalization era including the field of education. The IoT element has been widely engaged in higher education syllabus. However, in COVID 19 pandemic, the teaching and learning process for IoT becomes more challenging and difficult to deliver. As a solution, the Educational Kit for IoT Online Learning has been developed. This online learning kit will help students to practically learn the IoT without a face to face lecture. The objectives of the paper are to provide an overview of existing IoT education solutions and to develop IoT online learning kit. This learning kit consists of IoT development hardware and software which are equipped with a camera that connected to the online conference software. This paper will explain the development of the kit. Compared to other kits, this learning kit can directly be used for online learning and helps students to practice IoT at home, especially during a pandemic. On the other hand, IoT Online Kits is a pioneer in higher education for practical online learning.